Finland - Russia - Hamburg - Netherlands - Ireland [Motion Picture Film] - Herzfeld, Richard Phillip (1898-1980) (1962)
This film shows the North Cape Cruise on the M/S Gripsholm. Scenery of Helsinki, Helsinki Cathedral, Parliament building, statue of Czar Alexander I, University of Helsinki. Saint Petersburg (Leningrad), Assignation Bank Building, Peter and Paul Cathedral, St. Isaac's Cathedral, statue of Peter the Great (1782), Hermitage Museum. Peterhof Palace and gardens. Kremlin and Red Square, Church of the Twelve Apostles, Tsar Bell, Ivan the Great Bell Tower (Ivan Veliky), Spasskaya Tower, The Armoury (Oruzheynaya Palata), Eastern Entrance, Tsar Cannon, Arkhangelskiy Cathedral (The Cathedral of the Archangel), Saint Basil's Cathedral, Assumption Cathedral (Dormition Cathedral), Grand Kremlin Palace. Moskva River and University of Moscow. Kiel Canal and Elbe River. Hamburg, Panten un Blomen city park and gardens. Lubeck, Holstentor (Holsten Gate), market square, Rathaus (city hall). Netherlands, The Hague Peace Palace and gardens. Amsterdam fishing boats and canals, Scheveningen beach. Brussels, Belgium, city hall, Ducs (Dukes) of Brabant Hall on Grand Place. Ghent Clock Tower, Bruges canal scenes. Ireland, Dublin to Killarney landscape scenery. Ends on Three Crowns of Sweden's coat of arms. Color RBR Shelf; Silent